Impacts of Calcium Silicate Slag on the Availability of Silicon and Trace Contaminants in Rice (Oryza Sativa L.). Issue 2 (19th January 2019) - Yang, Rui; Howe, Julie A.; Golden, Bobby R.
ABSTRACT: Calcium silicate slag from the phosphorus fertilizer industry has the potential to be used as a liming agent or for silicon (Si) fertilization in rice production, but it contains trace elements that may contaminate rice grain and straw. A greenhouse study was performed to evaluate the bioavailability of Si and trace elements from slag (0, 1000, 2000, and 4000 mg kg −1 ) surface-applied or incorporated to a mineral soil and an organic soil. Slag application increased Si availability and rice grain yield relative to the control. Trace element and radioactivity in soil and rice grain were not significantly affected by slag supplementation. The applied slag showed minimal influence on plant available cadmium (Cd), chromium (Cr), or lead (Pb); however, copper (Cu) and zinc (Zn) in the organic soil increased, whereas Ni in the mineral soil decreased. Results indicate that the evaluated slag may be used as a Si fertilizer or liming amendment for rice with minimal environmental risks.